London, Paris, Berlin: economic competition and the new urban governance - NEWMAN, Peter; THORNLEY, Andy (European Spatial Research and Policy, 1994)
This article addresses the degree of autonomy experienced by the planning regimes of London, Paris and Berlin. What variation exists in the governance of these cities and how do national, local, political, business and community interests affect planning decisions? The discussion is placed in the context of the literature on world cities and growth coalitions and the debate over whether economic forces compel cities to follow similar strategies. The paper concludes that in the case of the three cities examined there is considerable variation of planning approach due to different historical, cultural and political factors.